Influence of the screw-thread rod matrix on the magnetic capture behavior of bastnaesite - Li, Wenbo; Sun, Junyan; Zhang, Xiaolong; Cheng, Shaokai; Ding, Xinhui (Powder technology, 2024)
High gradient magnetic separation (HGMS) is an effective method to recover fine weakly magnetic particles from suspension. The structural parameters of the magnetic matrix have a great influence on the distribution of the magnetic field in the separation space, which in turn affects the separation effect. This study investigated the magnetic adsorption behavior of high-gradient magnetic separator magnetic matrix parameters on different particle sizes of bastnaesite. Bastnaesite was obtained from Maoniuping, Sichuan, through experimental data and simulation analysis, the effects of structural parameters such as distance between equidistant ring-shaped bulges (ERB) and column gap between adjacent rods on the magnetic adsorption behavior of minerals with different particle sizes were investigated，and the force distribution of magnetic particles in the sorting space was analyzed. The results indicate that at any distance between ERB, the magnetic particle trapping effect of the staggered arrangement matrix is significantly superior that of parallel arrangement. Moreover, a column gap of 2 or 3 mm for the magnetic rods significantly outperforms trapping with a column gap of 4 or 5 mm. Under any rod gap, the trapping effect of the screw-thread rod matrix is better than that of the conventional rod matrix with the same diameter. In particular, the matrix has the optimal trapping effect on magnetic particles when the ERB distance is 1 mm. By analyzing the force distribution of bastnaesite in the sorting space, it is found that the matrix has poor trapping effect on fine-grained mineral particles. Under the same mineral particle size, increasing the magnetic field intensity can improve the recovery of useful minerals. [Display omitted] •The magnetic capture behavior of bastnaesite is studied by screw thread rod matrix.•The effect of matrix structural parameters on bastnaesite is preliminary determined.•The force of bastnaesite particles is analyzed by calculation.•The results of the bastnaesite test prove that the calculations are credible.